2012
DOI: 10.1097/sle.0b013e318242e549
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adrenalectomy in Children for Neuroblastoma

Abstract: The laparoscopic approach for adrenal neuroblastoma resection is feasible in children with good outcomes, but should be reserved to patients with small, well-circumscribed adrenal lesions, without invasive or infiltrative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Several studies, from a case series to multicenter studies for adrenalectomy and a large number of nephrectomies that examined MIS have been published, showing that MIS can be safely performed for malignant tumors. [9,11,22]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, from a case series to multicenter studies for adrenalectomy and a large number of nephrectomies that examined MIS have been published, showing that MIS can be safely performed for malignant tumors. [9,11,22]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on MIS for malignant diseases. Successful resection of NBL in 7 patients was reported in 2012 [9] . A study detailing 9 cases of laparoscopic malignant tumor resection of pediatric malignancies was published, 2 of which underwent open conversion [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the adrenal neuroblastoma's characteristic is invasion growth, the majority of patients in need of open surgery. There are many authors believe that the intraperitoneal is the better surgical approach, and can simultaneously bilateral adrenal exploration areas, and major bleeding complications [14].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 52 of 119 publications were related to the paediatric age: Numerous of these reports have described successful laparoscopic removal of the adrenal gland in children, and it is actually an accepted procedure to treat children with adrenal tumours; however, most of these studies included retrospective cohort studies, only a few prospective cohort studies were performed, missing randomised controlled trials or controlled clinical trials and long-term follow-up, so the advantages and disadvantages of laparoscopic in paediatric abdominal neuroblastoma still need to be defined, and the role of MIS in paediatric cancer is a matter of debate, and its use is limited to lesions that are small, well-circumscribed, without local infiltration or metastasis. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%